2021
DOI: 10.2147/jpr.s311559
|View full text |Cite
|
Sign up to set email alerts
|

Gate Mechanism and Parameter Analysis of Anodal-First Waveforms for Improving Selectivity of C-Fiber Nerves

Abstract: Purpose Few investigations have been conducted on the selective stimulation of small-radius unmyelinated C nerves ( C ), which are critical to both the recovery of damaged nerves and pain suppression. The purpose of this study is to understand how an anodal pulse in an anodal-first stimulation could improve C -selectivity over myelinated nociceptive Aδ nerves ( Aδ ) and to further clarify the landscape of the solution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that changes in the pulse rate can improve clinical outcomes 29 , 30 . In an experiment involving sinusoidal electrical stimulation, 2000 Hz selectively activated Aβ nerve fibers, 250 Hz activated Aδ fibers, and 5 Hz activated C fibers 31 . It can be assumed that a change in pulse frequency affects the activation of different nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that changes in the pulse rate can improve clinical outcomes 29 , 30 . In an experiment involving sinusoidal electrical stimulation, 2000 Hz selectively activated Aβ nerve fibers, 250 Hz activated Aδ fibers, and 5 Hz activated C fibers 31 . It can be assumed that a change in pulse frequency affects the activation of different nerve fibers.…”
Section: Discussionmentioning
confidence: 99%